Right Ventricle Dysfunction in COVID-19 Patients - Nikita P. Toding Labi; Agnes L. Panda; Edmond L. Jim (Universitas Sam Ratulangi, 2022)
Abstract: Coronavirus disease 2019 (COVID-19) has become a global pandemic. Related to its pathomechanisms and complications, COVID-19 is identified as a complex multi-organ disease. Cardiac involvement is reported in COVID-19 patients. One of the cardiovascular complications of COVID-19 is right ventricular dysfunction. This study aimed to provide an overview of right ventricular dysfunction in COVID-19 patients and its association with the patient's clinical outcomes. This was a literature review study conducted by searching and reviewing literatures on online databases as follows: PubMed, ScienceDirect, and ProQuest. There were 14 literatures obtained in this study with a total of 1,435 patients. All articles were observational studies conducted in January-April 2020 across various countries. Samples of patients with right ventricular dysfunction ranged from 3.6 to 41.7% of the total population of each study. Most studies defined right ventricle dysfunction as TAPSE<16-17 mm. Several echocardiography parameters and their threshold values were as follows: RV S' <9,5-10 cm/s; RVFAC <35%; right ventricular free wall strain (RVFWS); and right ventricular global longitudinal strain (RVGLS) according to ASE guidelines. In conclusion, right ventricular dysfunction has a high prevalence and is associated with poor outcomes of COVID-19 patients. Transthoracic echocardiography examination might become a risk stratification modality in hospitalized COVID-19 patients.Keywords: right ventricular dysfunction; coronavirus disease 2019; transthoracic echocardiographyÂ Abstrak: Coronavirus disease 2019 (COVID-19) telah menjadi pandemi global. Terkait dengan patomekanisme dan komplikasinya, COVID-19 dinyatakan sebagai penyakit multi-organ kompleks. Telah dilaporkan adanya keterlibatan jantung pada COVID-19. Salah satu komplikasi kardiovaskular dari COVID-19 ialah disfungsi ventrikel kanan. Penelitian ini bertujuan untuk memberikan gambaran disfungsi ventrikel kanan pada pasien COVID-19 dan hubungannya terhadap luaran klinis pasien. Jenis penelitian ialah literature review. Melalui penelusuran pada tiga database (PubMed, ScienceDirect, ProQuest), didapatkan 14 literatur dengan total 1.435 pasien. Semua artikel merupakan studi observasional yang dilakukan pada Januari-April 2020 dan tersebar di berbagai negara. Sampel pasien dengan disfungsi ventrikel kanan tercatat berkisar antara 3,6-41,7% dari total populasi tiap studi. Sebagian besar studi menetapkan definisi disfungsi ventrikel kanan dengan nilai TAPSE<16-17 mm. Beberapa parameter ekokardiografi lain beserta nilai ambang yang digunakan yaitu: RV S' <9,5-10 cm/s; RVFAC <35%; serta right ventricular free wall strain (RVFWS) dan right ventricular global longitudinal strain (RVGLS) berdasarkan panduan ASE. Simpulan penelitian ini ialah disfungsi ventrikel kanan pada COVID-19 memiliki prevalensi tinggi dan berhubungan dengan luaran pasien yang buruk. Pemeriksaan ekokardiografi transtorakal dapat menjadi modalitas stratifikasi risiko pada pasien COVID-19 yang dirawat inap.Kata kunci: disfungsi ventrikel kanan; coronavirus disease 2019; ekokardiografi transtorakal